Identifikasi Penyebab Kehilangan Crude Palm Oil (CPO) di Pabrik Kelapa Sawit - Mahmud Basuki; Iing Pamungkas; Tolu Tamalika (Jurnal Optimalisasi, 2023)
PT. Y is a company engaged in the processing of fresh palm fruit bunches into Crude Palm Oil (CPO), and has a production capacity of 30 tonnes/hour. The CPO production system generally goes through a long process and there are several processes that are not optimal. One of the processes is pressing, where this process experiences a lot of oil loss. Oil loss experienced at PT. Y of 6.28 to 6.32 percent of total production. Therefore, it is important to identify the causes of oil loss in the pressing process so that it becomes a preventive measure and can reduce the percentage of oil loss during the production process. The purpose of this research is to identify the factors that cause CPO oil loss and to recommend solutions to minimize CPO oil loss in screw press machines using fishbone diagrams. A fishbone diagram is used to identify the root causes of problems in a process. The cause of the problem is often caused by five elements, namely Man, Method, Machine, Material, and Environment. Fishbone diagram is useful for finding the factors that cause a problem. The results obtained from the fishbone diagram are several factors that cause oil loss in the pressing process or in the screw press machine including machine factors, raw materials, humans, and method factors. Recommendations that can be implemented by companies include routine maintenance of screw press machines, both corrective maintenance and preventive maintenance, it is necessary to control the quality of fresh fruit bunches from the beginning of harvest until the fruit reaches the loading ramp station, and this requires training so that operators can better understand how to machine operation.